Novel Chitosan Microparticles for Sequestration of Overdosed Drug - Chakraborty, Soma (Archīum Ateneo, 2017)
Chitosan microparticles were synthesized by crosslinking chitosan and glycidyl trimethylammonium chloride modified chitosan inside the reverse micelles of Span and Tween 80. The particles were of uniform size with the average diameter of 10 μm. The particles swelled almost twice the original size in 20 min when dispersed in a buffer solution of pH 7.4. The feasibility of chitosan microparticles as drug sequestrant was tested using propafenone as the model drug. The particles sequestered free propafenone from a buffer solution of pH 7.4. In 20 min unmodified chitosan and modified chitosan microparticles sequestered 53% and 51.5% of the free drug respectively. The amount of drug sequestered increased with increase in the initial free drug concentration. The presence of normal saline also improved propafenone sequestration.